Composite materials based on poly(N-isopropylacrylamide-co-methacrylic acid) hydrogels and calcium carbonate. (August 2015) - Doroftei, Florica; Mihai, Marcela; Sacarescu, Liviu; Fundueanu, Gheorghe; Simionescu, Bogdan C.
The synthesis of complex functional materials with thermo- and pH-sensitive tunable properties based on poly( N -isopropylacrylamide- co -methacrylic acid) hydrogels with different porosities and pH-sensitive and biocompatible calcium carbonate (CaCO3 ) was investigated. To control the composites characteristics, two hydrogles with the same chemical composition but different porosities were used, as well as different methods for crystal growth, namely, the adding protocol of inorganic partners (rapid mixing or alternate dipping) or the carbonate source. The morphology of the new composites was investigated by scanning electron microscopy and the polymorphs content by Fourier transform infrared spectroscopy, as compared to unmodified hydrogels. Information on the interface between organic/inorganic materials, the radii of gyration of the scattering objects, their fractal dimension, and CaCO3 porosity characteristics were obtained by small-angle X-ray scattering.